Gestão estratégica de tecnologia da informação com uso de BSC: uma pesquisa-ação em uma instituição pública federal brasileira - Knoll, Anne Camila (Universidade Federal de São Carlos, 2018)
This dissertation carries out the Strategic Reference Review of the Information Technology Master Plan of a federal public institution of basic and technological education, aiming to provide an improvement in the elaboration in the Information Technology Master Plan of the institution and to contribute with the implementation of strategic management based in Balanced Scorecard in the area of ​​Information Technology of the organ. The motivation of the research is based on legal planning obligations by the federal public administration bodies and the incentive and supervision of the control bodies so that this obligation is applied to the IT area of ​​the organs. The methodology used is that of action research, consisting of the participation of IT staff members of the research institution and was carried out using an adaptation of the schedule proposed by the creators of the BSC, Kaplan and Norton, to guide the interviews and meetings that result in the construction of a strategic map for the IT area of ​​the organ. The stages of the research consist of a theorical survey about the subject, the accomplishment of interviews, analyzed by the methodology of Content Analysis, that served as reference for meetings of consensus on the strategy that used the method of Oval Maping Technique, generating like result the Strategic Map and the strategic indicators framework of the IT area of ​​the research institution.
Keywords: Tecnologia da Informação; Planejamento estratégico; IT-BSC; Balanced scorecard; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA